Uji Antidiabetes pada Ekstrak Buah Alpukat (Persea americana) Menghambat α-Amylase secara in silico - Sari, Lisa Permata; Amelia, Fitri (Departemen Kimia FMIPA UNP, 2025)
DM is a metabolic disorder characterized by chronic high blood glucose levels that can cause death. Long-term hyperglycemia can slowly cause retinopathy, heart and blood vessel disease, and neuropathy. Avocado is known to be used as an anti-diabetic because it contains saponin, alkaloid, steroid, phenol, tannin dan glikoside that are effective in lowering blood glucose levels. This study aims to test the potential for inhibition of the α-amylase enzyme using the molecular docking method. The study was conducted by utilizing a protein that has PDB ID 2QV4 to interact with active compounds in the ethanol extract of Avocado fruit. The results obtained were that the compounds procyanidin, vitexin, dan isoharment rhamnoside have good binding ability to α-amylase. Thus, these compounds have the potential as antidiabetics.